Green and low carbon matters: A systematic review of the past, today, and future on sustainability supply chain management practices among manufacturing industry - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud; Sorooshian, Shahryar; Adeleke, A. Q. (Elsevier Ltd, 2021)
Climate change has arisen as one of human beings' most significant threats. A higher proportion of carbon dioxide emissions are produced from developing countries as manufacturing globalization requires more and more emerging nations. The predicament between carbon reduction and fast industrial development makes firms in developing countries reluctant to take thoughtful commitment and actions in carbon dioxide emission reduction in their global manufacturing practices. Sustainability, green, and low-carbon supply chain networks research is still also in its infant stage from a theoretical perspective and requires further research and development. Therefore this research aims to address the research question: “Why and how organizations are adopting sustainable strategies in developing countries to increase sustainable supply chain management practices in the manufacturing?“. In order to thoroughly analyse the literature, this paper used ATLAS.ti 9 software tools to save, identify, and assess the data for this study. We reviewed, compiled, and sorted papers from 326 publications for this article and then recognized 141 as critical to the work scope. The results reveal that the organization's current concentration is on improving internal environmental efficiency related to its mid-stream SCM activities. The introduction of environmental practices at the external level (downstream and upstream) is relatively limited, and few organizations are collaborating effectively with supply chain partners to improve their SSCM performance. The results also show that organizational performance, reputation/risk management, customer pressure, and top management support are primary motivators for organizations to embrace SSCM practices. The typology suggests that companies need to consider and recognize their key sustainability risk in the past, current, and future to have a simple organizational design to innovative management methods to handle their sustainable supply chain practices.